Molecular and Cellular Mechanisms Underlying the Initiation and Progression of Alport Glomerular Pathology - Cosgrove, Dominic; Madison, Jacob (Frontiers in Medicine, 2022)
Alport syndrome results from a myriad of mutations in the COL4A3, COL4A4, or COL4A5 genes that encode type IV (basement membrane) collagens. Unlike type IV collagen α1(IV)2α2(IV)1 heterotrimers, which are ubiquitous in basement membranes, α3/α4/α5 have a limited tissue distribution. The absence of these basement membrane networks causes pathologies in some, but not all these tissues. Primarily the renal glomerulus, the stria vascularis of the inner ear, the lens, and the retina as well as a rare link with aortic aneurisms. Defects in the glomerular basement membranes results in delayed onset and progressive focal segmental glomerulosclerosis ultimately requiring the patient to undergo dialysis and if accessible, transplant. The lifespan of patients with Alport syndrome is ultimately significantly shortened. This review addresses the consequences of the altered glomerular basement membrane composition in Alport syndrome with specific emphasis on the mechanisms underlying initiation and progression of glomerular pathology.